ANALISIS PENGARUH ATRIBUT PRODUK TERHADAP LOYALITAS KONSUMEN - Robert Fransiska (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
In the world of marketing, marketing strategy is crucial. This course requires the active role of marketers in order to create innovative marketing strategies and effective way to reach consumers. Appropriate marketing strategy would benefit the company because it will be able to create customer loyalty. Honda is one of the motorcycle brand to a multi-branding strategy, the strategy of launching new products with new attributes in a single category of the same parent brand. The level of sales experienced an increase trend from year to year. Trend is especially true in the area Palangka Raya city.This study analyzes the influence of multi-branding strategy of Honda withits new product attributes of quality (X1), keiritan fuel (X2), product design (X3), services (X4), and the price (X5) customer loyalty (Y) . Analysis model used was multiple linear regression. Previously, testing the validity and reliabelitas, along with the classic assumption test of research data.Test results using multiple linear regression with the F test result in the conclusion that among the five variables that product attributes included in the models, namely quality (X1), keiritan fuel (X2), product design (X3), services (X4), and the price (X5 ), only three of which have a significant influence on customer loyalty (Y). The third variable is the quality (X1), fuel keiritan (X2), and services (X4). Three variables have a significance value smaller than 0.05, or in other words t-counted value is greater than t tables of 1.984. This partial test results concluded that the fuel keiritan (X2) is the variable most dominant influence on customer loyalty (Y). This can be seen from the calculated t value greater than t count the two other variables, namely for 4,932.Keywords : influence, customer loyalty, product attributes